2D molecular precursor for a one-pot synthesis of semiconducting metal sulphide nanocrystals - Bera, Abhijit; Prasad, Bhagavatula L. V. (Bulletin of Materials Science, 2018)
2D molecular materials, namely, metal alkyl thiolates, have been used as a single-source precursor for the synthesis of semiconducting metal sulphide nanocrystals (NCs) by thermal decomposition. These 2D molecular precursors have all the ingredients required for metal sulphide synthesis (metal source, sulphur source and protecting ligand). In this study, we demonstrate a simple and general solvothermal decomposition' approach for the synthesis of high-quality , PbS, CdS, MnS and ZnS NCs. The size of the NC can also be controlled by changing the decomposition temperature. Furthermore, the optical properties of the NCs have also been studied.